Does in-role performance mediate the relationships between performance appraisal, internal communication and customer satisfaction - Salahat, Mahmoud; Abdul Majid, Abdul Halim (2017)
Palestinian insurance customers are not satisfied. 55% of them changed their companies in 3 years or less.44% of customers are willing to switch and 30% of customers think that the perceived insurance services are below their expectations. Further, prior literature paid less attention to internal organizational factors contributing to customer satisfaction.This study is aiming to examine the impact of performance appraisal and internal communication on CS. and then test the mediating role of in-role performance between these variables.The findings revealed performance appraisal and internal communication have a direct effect on CS. furthermore, in-role performance plays a partial mediating role performance appraisal and internal communication respectively and CS. based on current study findings, insurance companies in Palestine have to give more attention to develop performance appraisal and internal communication to solve the current problems of CS.